Biochemical profiling of Pakistani sorghum and millet varieties with special reference to anthocyanins and condensed tannins. Issue 1 (1st January 2018) - Ahmad, Farah; Pasha, Imran; Saeed, Muhammad; Asgher, Muhammad
ABSTRACT: Cereals like sorghum and millet are splendid sources of phenolics, dependent on their genetic makeup, and possess varied levels of flavonoids, flavanols, flavanones, anthocyanins, and condensed tannins. In this study, chemical composition and anthocyanin and tannin content of seven sorghum and two millet varieties were evaluated. American Association of Cereal Chemists (AACC) respective methods were used for chemical composition. Anthocyanins were determined through HPLC/UV-Vis, while condensed tannins were determined spectrophotometrically. Four anthocyanins determined included apigeninidin, kuromanin, pelargonidin, and cyanidin. Among sorghum varieties, JS-263 had the highest apigeninidin (16 µg/g). Other anthocyanins were not found in appreciable quantities. None of the anthocyanins were detected in millet varieties. Condensed tannins were highest in sorghum variety PC-1 (179.76 mg/100g) and millet variety S. Bajra-2011 (172.75 mg/100g). Two varieties, one each from sorghum and millet, were selected for extraction of bran as a separate fraction. Brans were modified by size reduction and enzymatic treatment (xylanase and cellulase). Enzymatic treatment favorably affected the extraction of phenolic compounds like anthocyanins. Sorghum and millet flour- and bran-supplemented breads were also developed and evaluated for sensory acceptability.